Educação ambiental: um estudo nos terceiros anos das escolas públicas do município de Santana do Livramento/RS - (:unkn) unknown (Universidade Federal do Pampa, 2017)
In order to emphasize environmental issues, taking into account the aggravation of global environmental problems, which can be reversed or minimized through the correct attitudes of the human being and school being one of the main influential environments of change in the conduct of each individual, It was necessary to analyze the work of Environmental Education carried out within the third years of public schools in the city of Santana do Livramento. The choice of respondents' schooling is justified by the fact that the third-year students are saying goodbye to school and sought to know if they are carrying a load of environmental awareness acquired within the school environment for adulthood that Are about to enter. Thus, the main objective of this research is to analyze how the Environmental Education study is developed in the third years of six state public schools in the municipality of Santana do Livramento. This study was carried out through a quantitative approach, method of survey and descriptive character, with application of structured questionnaire with closed questions in third year students of the morning shift of six public schools. Data analysis was performed using tabulation using the Excel program and the data were generated through the SPSS program (Statistical Package for Social Science for Windows), which is a software used for statistical analysis of the data. As results, it is possible to emphasize that the majority of the students possess knowledge and interest on the subject, considering this school base fundamental for their own conscientization. However, it was noted that students feel the need for more practical and dynamic activities focused on the subject and that schools do little or nothing to this effect to attract students' interest in the subject.
Environmental education: a study in the third years of public schools in the municipality of Santana do Livramento / RS
Keywords: Administração; Escola pública; Educação ambiental; Environmental education; Public schools; CNPQ::CIENCIAS SOCIAIS APLICADAS